2010
DOI: 10.4103/0973-1296.66932
|View full text |Cite
|
Sign up to set email alerts
|

Production of podophyllotoxin in Linum linearifolium in vitro cultures

Abstract: For the first time, callus and suspension cultures of Linum linearifolium were initiated. Podophyllotoxin (PTOX), a strong antitumor precursor, was isolated from the calli and suspension, as a main lignan besides smaller amount of 6-methoxypodophyllotoxin (6MPTOX). L. linearifolium is now the third Linum species of section Syllinum, with PTOX as the main lignan. The amounts of lignans, especially PTOX, found in L. linearifolium cell cultures are quite high within the studied Linum species until now. The antipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Plant material and in vitro cultures:Seeds from wild Linum thracicum ssp. thracicum plants (Linaceae) were collected near Asenovgrad, Bulgaria in July 2012 and used for initiation of aseptic in vitro cultures, as previously described[5]. Cell suspension cultures were cultivated in full strength (Li) and half strength (HS) liquid Murashige and Skoog medium[18] supplemented with 0.4 mg/L α-naphthaleneacetic acid.…”
mentioning
confidence: 99%
“…Plant material and in vitro cultures:Seeds from wild Linum thracicum ssp. thracicum plants (Linaceae) were collected near Asenovgrad, Bulgaria in July 2012 and used for initiation of aseptic in vitro cultures, as previously described[5]. Cell suspension cultures were cultivated in full strength (Li) and half strength (HS) liquid Murashige and Skoog medium[18] supplemented with 0.4 mg/L α-naphthaleneacetic acid.…”
mentioning
confidence: 99%
“…were found in the concentration of caffeic acid, quercetin, luteolin and MQ between these tissue lines (Table 1). It was previously shown that the production of phenolics in cultures is highly dependent on plant growth regulators 30 and that growth regulators have higher impact on phenolics' production than changes of nutrient salt concentration in basal medium. 24 The results obtained for in vitro grown tissues are in accordance with these findings.…”
Section: Resultsmentioning
confidence: 99%
“…The production of 2,7′‐cyclolignans by plant tissue cultures has been extensively reviewed [12,15,49–52], and different biological systems from quite a large variety of species have been evaluated for their capacity to accumulate 2,7′‐cyclolignans: Podophyllum spp., Linum spp., Haplophyllum patavum, Juniperis chinensis and Callitris drummondii among others.…”
Section: The Tissue Culture Approachmentioning
confidence: 99%